Large-Scale and Template-Free Growth of Free-Standing Single-Crystalline Dendritic Ag/Pd Alloy Nanostructure Arrays - Wang, D.; Li, T.; Liu, Yang; Huang, J.; You, T. (American Chemical Society, 2009)
Large-scale arrays consist of dendritic single-crystalline Ag/Pd alloy nanostructures are synthesized for the first time. A simple galvanic replacement reaction is introduced to grow these arrays directly on Ag substrates. The morphology of the products strongly depended on the reaction temperature and the concentration of H2PdCl4 solution. The mechanism of the formation of alloy and the dendritic morphology has been discussed. These alloy arrays exhibit high surface-enhanced Raman scattering (SERS) activity and may have potential applications in investigation of “in situ” Pd catalytic reactions using SERS. Moreover, electrocatalytic measurements suggest that the obtained dendritic Ag/Pd alloy nanostructures exhibit electrocatalytic activity toward the oxidation of formic acid.